A Descriptive Study of EFL University Students’ Difficulties in Understanding Implicit Meanings in Opinion Texts - Dinda Ariyanti; Seful Bahri (Journal of Educational Sciences, 2026)
Understanding implicit meanings is essential to critical reading because opinion texts often communicate positions, assumptions, and implications without stating them directly. This study explored EFL university students’ difficulties in interpreting implicit meanings in opinion texts and the strategies they reported using. A descriptive qualitative design was employed with 30 English Education students at Universitas Negeri Semarang who had completed a Critical Reading course; the sample comprised 23 eighth-semester students, 2 sixth-semester students, and 5 fourth-semester students. Data were collected through a Google Forms reading test containing two opinion texts, twelve open-ended comprehension questions, and three reflective questions. The responses were analyzed thematically, with descriptive frequencies used to indicate theme occurrence. The main difficulty was connecting textual clues across sentences or paragraphs to infer unstated messages, reported by 26 participants (86.7%). Rereading and careful reading was one of the most common strategies, reported by 18 participants (60.0%). However, strategies were not always applied systematically. The study concludes that explicit instruction should guide students in identifying textual evidence, connecting clues, and evaluating alternative interpretations, while the uneven cohort distribution should be considered when interpreting the findings.